2019
DOI: 10.1175/jtech-d-18-0173.1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Performance Characteristics of the Lightning Imaging Sensor

Abstract: The Lightning Imaging Sensor (LIS) that was on board the Tropical Rainfall Measuring Mission (TRMM) satellite captured optical emissions produced by lightning. In this work, we quantify and evaluate the LIS performance characteristics at both the pixel level of LIS events and contiguous clusters of events known as groups during a recent 2-yr period. Differences in the detection threshold among the four quadrants in the LIS pixel array produce small but meaningful differences in their optical characteristics. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 46 publications
4
33
0
Order By: Relevance
“…For an enhanced understanding of the flash detection by ISS-LIS and Meteorage, characteristics of the flashes are investigated. In accordance with, e.g., Rudlosky et al (2017) and Zhang et al (2019), the probability of a match increases with a larger flash extent and flash duration. A matched flash extended on average almost twice as wide and lasted twice as long as a flash not seen by both ISS-LIS and Meteorage.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…For an enhanced understanding of the flash detection by ISS-LIS and Meteorage, characteristics of the flashes are investigated. In accordance with, e.g., Rudlosky et al (2017) and Zhang et al (2019), the probability of a match increases with a larger flash extent and flash duration. A matched flash extended on average almost twice as wide and lasted twice as long as a flash not seen by both ISS-LIS and Meteorage.…”
Section: Discussionsupporting
confidence: 71%
“…Those values are in accordance with the distances observed by Rudlosky et al (2017) between TRMM-LIS flashes and GLD360 strokes. Zhang et al (2019) thoroughly investigated TRMM-LIS performance and found additional latitudinal location offset resulting from TRMM yaw maneuvers. Their analysis suggests a correction for TRMM-LIS group locations that improves the TRMM-LIS group distance to NLDN pulses and/or strokes for the summers of 2012 and 2013.…”
Section: Distances and Timing Offsets Between Collocated Flashesmentioning
confidence: 99%
“…is used in this report to convert long-term LIS group radiance values to cloud-top energy. In addition, the approximate nighttime minimum detection threshold for LIS can be derived using equations A4 or A5 along with knowledge of the minimum pixel radiance threshold that was recently characterized by Zhang et al (2019). These authors found minimum detected radiance (spectral energy density) values of 2.9 to 3.6 μJ/m 2 /ster/nm, depending on the quadrant in the LIS pixel array.…”
Section: Equation A5mentioning
confidence: 99%
“…They cannot, however, directly observe the polarity, altitude, CG versus IC classification, or the number of strokes (i.e., the multiplicity) in a given flash. Moreover, the optical signals may be modified by scattering in the surrounding cloud medium (Peterson et al, 2017a;Peterson, Rudlosky, et al, 2017) or variations in LIS sensitivity due to instrument performance (i.e., Charge-Coupled Device array pixel and quadrant, Zhang et al, 2018) and background radiance ( Figure 3 in Peterson & Liu, 2013), even to the point of preventing detection entirely.…”
Section: Introductionmentioning
confidence: 99%